HUKUM MELUPAKAN HAFALAN AL-QUR’AN - Dahliati Simanjuntak (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
The main problem in this journal is about people who have memorized the Qur'an. What is the law if someone has memorized the Qur'an, then he forgets to memorize it. So in this journal hadiths related to the threat of forgetting to memorize the Qur'an will be reviewed or discussed. As it is known that forgetting is a trait that is owned by all humans, including a hafidz. In a hadith it is explained that the Prophet also forgot a verse. Forget what the hadith means. This is where the author is interested in discussing it in a journal.